Adopted Children of Civil Servants According From Islamic Law: Legalitas Anak Angkat Pegawai Negeri Sipil Dalam Perspektif Hukum Islam - Khairani, Khairani; Zahara, Mulyana (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Law Number 39 of 1999 concerning Human Rights regulates children's rights, the implementation of the obligations and responsibilities of parents, families, communities, the government, and the state to provide protection for children. However, these children can be categorized into 2 parts, namely adopted children and biological children. However, there are many problems with child adoption in Banda Aceh that aim to adopt children, especially civil servants, not only because they want to have children or help children and give love, but because there are civil servant allowances. This raises problems with adoptive parents including adopted children as recipients of child allowances for civil servants and Islamic law reviewing children who are used as biological children in state administration. The purpose of this research is to determine the factors affecting adopted children as recipients of civil servant allowances and to understand the Islamic Law review of adopted children who are used as biological children in the state administration. In this research the author used qualitative research methods and a juridical approach. Based on the research results, the factors that lead to adopting children as recipients of child allowances for civil servants are not having children, the economic condition of biological parents, earning more money and the welfare of the child. According to Islamic law, it is permissible and even recommended to adopt children. However, including children on the payroll aims to provide a decent life for children, not to seek personal gain. The adoption of a child to receive child support on the payroll is justified by conditions permitted by law or in a formal legal manner.